A DEVELOPMENT OF GOOGLE FORM-BASED PERSONALITY TYPOLOGY INVENTORY FOR STUDENTS AT SMP NEGERI 3 MAPILLI - Sitti Hajar; Abdullah Pandang; Sahril Buchori (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to develop a valid, reliable, and practical Google Form-based Personality Typology Instrument for students at SMP Negeri 3 Mapilli. The background of this study is based on the results of a needs analysis that shows the limitations of personality assessment instruments in schools and the low level of students' understanding of their personality types and learning styles. These conditions have an impact on students' difficulty in understanding lesson material and low level of learning independence. Therefore, a personality assessment instrument that is easy to use, efficient, and suitable for the characteristics of students in the digital era is needed. This study uses the research and development method. The development procedure includes the stages of needs analysis, planning, prototype instrument development, validation by subject matter experts and media experts, product revision, and practical testing. The test subjects involved students and homeroom teachers of SMP Negeri 3 Mapilli. Data were collected through interviews, questionnaires, and observation sheets, then analyzed descriptively, quantitatively, and qualitatively. The results showed that the developed instrument had an excellent level of validity, with an average expert validation percentage of 85 percent, placing it in the highly valid category. The practicality test showed high results, with an achievement percentage between 80 and 99 percent, which falls into the practical to highly practical category. These findings indicate that the instrument is easy to use and accepted by users. Thus, the Google Form-based Personality Typology Instrument is declared suitable for use as a student personality assessment tool to support more effective, adaptive, and individual-oriented learning.